Co-Operative Inquiry : Research into the Human Condition. - Heron, John (Sage Publications, 1996)
This is the first book to provide a comprehensive account of co-operative inquiry: a way of doing research with people where the roles of researcher and subject are integrated. Co-operative inquiry is a distinctive and wide-ranging form of participative research in which people use the full range of their sensibilities to inquire together into any aspect of the human condition. This book offers both an extensive exploration of its theoretical background and a detailed practical guide to the methods involved. Topics covered include: a critique of established research techniques; the underlying.